Isolation and study of several isolates of Tobacco mild green mosaic virus (Tobamovirus) on Nicotiana glauca Graham in Libya - Ejmall, Mahjob A.; EL-Sanousi, Omar M.; EL-Ammari, Salah S. (Al-Mukhtar Journal of Sciences, 2009)
Nicotiana glauca Commonly shows mosaic symptoms along the costal regions of Libya. To identify the causal virus, 25 samples were randomly collected from different areas in the western part of the costal belt region. Using ELISA, one isolate showed the presence of tobamovirus alone whereas in several samples this virus was found together with cucumber mosaic virus. Symptomology and host range studies approved that these isolates belongs to Tobacco mild green mosaic virus (TMGM). These isolates have he simility in symptoms induced on 13 plant species, differences on 10 hosts and not infected other 10 plant species. Properties of the virus in crude sap revealed that all virus isolates have thermal inactivation point was between 84°C and 88°C; dilution end point (DEP) was between 10-2 -10-3 and Longevity in vitro (LIV) was more than one year.